2016
DOI: 10.1177/0141076816634317
|View full text |Cite
|
Sign up to set email alerts
|

The impact of team familiarity and surgical experience on operative efficiency: a retrospective analysis

Abstract: Objectives: The independent impact of individual surgical experience and team familiarity on surgical performance has been widely studied; however, the interplay of these factors and their relative, quantified, contributions to performance is poorly understood. We determined the impact of team familiarity and surgeon, and cumulative team experience on operative efficiency in total knee replacement. Design: Retrospective analysis of all total knee replacements conducted at the host institution in 1996-2009. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 25 publications
(35 reference statements)
0
55
0
Order By: Relevance
“…Inconvenience events lead to prolongation of surgery times, which is associated with higher costs and less favourable clinical outcomes 5 25 29 30. This goes in hand with prior studies that demonstrated the benefit of both surgical experience and team familiarity 17. This establishes the potential importance of considering these factors when the aim is to improve surgical efficiency and patient safety, and also opens new opportunities and creates new challenges for quality improvement strategies for RAS.…”
Section: Discussionmentioning
confidence: 70%
“…Inconvenience events lead to prolongation of surgery times, which is associated with higher costs and less favourable clinical outcomes 5 25 29 30. This goes in hand with prior studies that demonstrated the benefit of both surgical experience and team familiarity 17. This establishes the potential importance of considering these factors when the aim is to improve surgical efficiency and patient safety, and also opens new opportunities and creates new challenges for quality improvement strategies for RAS.…”
Section: Discussionmentioning
confidence: 70%
“…62 It has been demonstrated that a high level of familiarity decreases the number of interruptions, 28,36,49 improves the performance of the surgical team by decreasing the duration of the surgical procedure 63 and postoperative complications, 64 and by promoting teamwork and communication. 65 •Technology. Interruptions related to equipment problems represented the highest risk of significant impact on the surgical procedure.…”
Section: Protagonists Of Interruptionsmentioning
confidence: 99%
“…Maruthappu et al 26 focused on perioperative outcomes in total knee replacements and correlation with surgical experience and team familiarity. Although surgical experience has been previously shown to positively impact on performance,27–29 this study furthered this concept by investigating collective experience of the team members to build on ElBardissi et al ’s study 30.…”
Section: The Effect Of Collaboration and Familiaritymentioning
confidence: 99%